Selecting and coordinating local and regional climate change interventions. (November 2016) - Culotta, Daniel; Wiek, Arnim; Forrest, Nigel
Local and regional organizations are designing and implementing interventions to mitigate greenhouse gas emissions through various programs and projects. These efforts have been less effective than anticipated, and emissions have continued to rise. Because awareness, intent, planning, and actions are all present, yet results not being achieved, the processes organizations use to select interventions may be insufficient. We derive criteria to assess intervention selection processes from the literature and use them to evaluate the intervention selection processes of a county-wide climate change mitigation initiative in Sonoma County, California. The initiative in Sonoma County is far short of its 2015 emissions reduction goal. Our analysis suggests the initiative's process has shortcomings including poor coordination, a focus on end-use emissions instead of systemic solutions, and short-term opportunism. We also find that the governance of the county-wide initiative may also have been a significant factor in failing to achieve the goal.